Wybrane aspekty aktywności edukacyjnej i zawodowej młodych osób z niepełnosprawnościami - Jarmużek, Joanna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The aim of the publication is to present selected aspects of starting adult life by the people with disabilities. Young adults, entering adult life, verify their plans and life goals, and tries to fulfill the life tasks typical of this stage in a satisfactory way. In certain special situations (such as disability), meeting these challenges can be difficult. The article will discuss selected aspects of the educational and occupational activity of young people with disabilities.